Cause Related Marketing Strategy (Business Strategy Based on Sustainable Indonesian Community Local Wisdom) - Arya Surendra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic has had an impact on various aspects of human life, including the economic aspect. One of the causes of the economic decline in Indonesia is the low purchasing power of the people, so that the economic cycle in society cannot run smoothly. The strategy that is commonly carried out by the Indonesian people is based on local wisdom trying to share some of the profits for people in need, this in economic language is often called a cause related marketing strategy (CRM). Cause Related Marketing is a business strategy based on local wisdom by being directly involved in social activities in the community, so as to improve the company's positive image in a sustainable manner.